Memorandum on Reduction in Cost of Major Construction Projects - Planning Commission (Planning Commission, Government of India, 1962)
The memorandum issued by the Planning Commission of the Government of India presents a strategic framework for reducing the cost of major construction projects while maintaining efficiency and quality in public infrastructure development. Recognizing that construction activities often account for nearly half of the expenditure in sectors such as power, irrigation, and public services, the document emphasizes the need for systematic cost management through improved planning, organization, and execution practices. A key recommendation is the establishment of specialized cost reduction units for major projects, which would analyze materials, construction techniques, and administrative procedures to identify opportunities for savings without compromising functionality or durability. Complementing this initiative, the memorandum proposes the formation of state-level committees to ensure coordinated implementation of cost reduction strategies across various government agencies. The report highlights the importance of detailed pre-construction planning, including feasibility studies, site assessments, appropriate scheduling, and phased project implementation to prevent resource inefficiencies and delays. Since materials represent a significant proportion of construction costs, effective inventory control and careful procurement practices are recommended to balance the need for steady supply with the avoidance of excessive stockholding. The memorandum also examines different execution models, suggesting that departmental execution can provide stronger oversight and potential cost savings, while smaller local contractors may offer economic advantages due to lower operational overheads. Timely payment to contractors and clearly structured payment schedules are emphasized to prevent financial strain and unnecessary cost escalations. Furthermore, the preparation of comprehensive completion reports and the adoption of post-audit systems are recommended to streamline project delivery and provide valuable documentation for future reference. The memorandum also stresses the importance of continuous training and professional development for personnel involved in construction management to improve technical competence and cost efficiency. Overall, the document outlines a comprehensive approach combining administrative reforms, financial discipline, improved project management practices, and skill development to achieve substantial cost savings in public construction projects while supporting broader national development objectives.
Government of India, Planning Commission New Delhi June, 1962
Keywords: Construction Cost Reduction; Major Construction Projects; Cost Reduction Units; State-Level Committees; Pre-Construction Planning; Inventory Control in Construction; Departmental Execution Method; Contractor Management; Payment Scheduling; Completion Reports and Audits; Construction Cost Management; Training and Skill Development